A widely expressed free immunoglobulin κ chain with a unique Vκ4-1/Jκ3 pattern promotes colon cancer invasion and metastasis by activating the integrin β1/FAK pathway. (1st August 2022) - Wang, Qianqian; Jiang, Dongyang; Ye, Qing; Zhou, Wenjing; Ma, Junfan; Wang, Chong; Geng, Zihan; Chu, Ming; Zheng, Jie; Chen, Hongchengcheng; Huang, Jing; Dai, Hui; et al.
Abstract: Historically, immunoglobulin (Ig) has been known as an antibody and is expressed only in B lineage cells; importantly, Ig light chains are conjugated to heavy chains to form intact Igs. However, in this study, we found a free Igκ light chain with a unique Vκ4-1/Jκ3 rearrangement (Vκ4-1/Jκ3-FLC) that was widely expressed in different non-B lineages and was overexpressed in cancer cells. Further study indicated that Vκ4-1/Jκ3-FLC was hydrophobic, formed obvious insoluble deposits in the extracellular matrix (ECM) and existed in free form. Functional analyses demonstrated that Vκ4-1/Jκ3-FLC promoted the proliferation, migration and metastasis of colon cancer cells in vitro and in vivo . Mechanistically, Vκ4-1/Jκ3-FLC bound to integrin β1 and activated the FAK and Src pathways. More importantly, specific antibodies against the variable region of Vκ4-1/Jκ3-FLC significantly inhibited the growth of colon cancer tumors. Our findings suggested that Vκ4-1/Jκ3-FLC is a novel ECM protein and integrin β1 ligand and that it is involved in cancer progression and is a potential therapeutic target in cancer, particularly colon cancer. Graphical abstract: Image 1 Highlights: The immunoglobulin κ chain with a unique Vκ4-1/Jκ3 pattern is widely expressed in cancer cell. Vκ4-1/Jκ3-Igκ is a hydrophobic FLC potentially located in the ECM and promotes cancer progression. Vκ4-1/Jκ3-FLC interacts with integrin β1 and promotes cancer cells growth and migration via activating the FAK signaling. Vκ4-1/Jκ3-FLC might be a novel therapeutic target in many cancers, such as colon cancer.